2013
DOI: 10.1111/1567-1364.12103
|View full text |Cite
|
Sign up to set email alerts
|

Aging and differentiation in yeast populations: elders with different properties and functions

Abstract: Over the past decade, it has become evident that similarly to cells forming metazoan tissues, yeast cells have the ability to differentiate and form specialized cell types. Examples of yeast cellular differentiation have been identified both in yeast liquid cultures and within multicellular structures occupying solid surfaces. Most current knowledge on different cell types comes from studies of the spatiotemporal internal architecture of colonies developing on various media. With a few exceptions, yeast cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 53 publications
(133 reference statements)
1
37
0
Order By: Relevance
“…Over the past years, evidence has been accumulating in support of the idea that unicellular yeast are able to differentiate into specialized cell types and could therefore serve as a primitive model of developing metazoan tissues (for review Palková et al 2014). In the present study, we approached the differentiation of chronologically aged yeast liquid cultures from the perspective of cell size, as we observed that the size distribution profiles of cultures changed during cultivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past years, evidence has been accumulating in support of the idea that unicellular yeast are able to differentiate into specialized cell types and could therefore serve as a primitive model of developing metazoan tissues (for review Palková et al 2014). In the present study, we approached the differentiation of chronologically aged yeast liquid cultures from the perspective of cell size, as we observed that the size distribution profiles of cultures changed during cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a growing body of evidence shows that, on reaching stationary phase, yeast cells differentiate into several subpopulations with distinct physiology, whether grown in liquid culture or as colonies on solid medium (Allen et al 2006; Palková et al 2014). This finding has opened up a new field of study of unicellular yeast differentiation, which may help us to understand the development of higher-eukaryotic tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Sporulation occurs under the specific condition of active respiration (NFCs being much higher than FCs), high pH, and depleted nitrogen and/or other nutrients (reviewed in 156157). Quiescence, like sporulation, is triggered by the absence of at least one essential growth nutrient and alkaline pH, but (unlike sporulation) quiescence does not have a requirement for respiration (reviewed in 10158. Finally, pseudohyphal differentiation occurs at intermediate-to-low nitrogen concentrations (reviewed in 135), can also be induced by other cues such as fusel alcohols, and also responds to other cues in some strain backgrounds (reviewed in 159).…”
Section: Varying Fates Varying Functionsmentioning
confidence: 99%
“…Although quiescence can be induced in a range of environments, extracellular environment strongly influences the properties of Q cells. For example, metabolic and other biological properties of Q cells vary depending on which nutrient is limiting (reviewed in 10164). These different properties suggest the existence of multiple types of Q cells depending on the presence or absence of particular environmental cues.…”
Section: Varying Fates Varying Functionsmentioning
confidence: 99%
See 1 more Smart Citation